Glucose administration inhibits the hepatic activation of gluconeogenesis promoted by insulin-induced hypoglycemia - Galende,Sharize Betoni (2009)
The activation of hepatic gluconeogenesis in male Wistar adult 6 h fasted rats during insulin-induced hypoglycemia (IIH) was previously demonstrated. In this study, the effects of intraperitoneal (ip) glucose (100 mg/kg) on the activation of liver gluconeogenesis during IIH was investigated. Thus, 6 h fasted rats that received ip regular insulin (1 U/kg) and 30 min later ip saline (Control group) or glucose (Experimental group) were compared. All the experiments were executed 60 min after insulin injection. The glycemia of Control and Experimental groups were not different (P > 0.05). To investigate gluconeogenesis, liver perfusion experiments were performed. The results demonstrated that excepting glycerol, livers from rats which received ip glucose showed lower (P < 0.05) gluconeogenesis from L-alanine, L-glutamine, L-lactate or L-alanine + L-glutamine + L-lactate + glycerol. Therefore, the absence of glucose recovery after the glucose administration was mediated, at least in part, by an inhibition of hepatic gluconeogenesis.